2019
DOI: 10.3390/cancers11070908
|View full text |Cite
|
Sign up to set email alerts
|

Wnt-11 as a Potential Prognostic Biomarker and Therapeutic Target in Colorectal Cancer

Abstract: The expression of the secreted factor Wnt-11 is elevated in several types of cancer, including colorectal cancer, where it promotes cancer cell migration and invasion. Analysis of colorectal cancer gene expression databases associated WNT11 mRNA expression with increased likelihood of metastasis in a subset of patients. WNT11 expression was correlated with the expression of the Wnt receptors FZD6, RYK, and PTK7, and the combined expression of WNT11, FZD6 and RYK or PTK7 was associated with an increased risk of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 51 publications
2
15
0
Order By: Relevance
“…Another study has presented miR-410 expression was reduced in human estrogen receptor-positive tissues of breast cancer [24]. It is reported that secreted factor Wnt-11 expression is ascended in several types of cancer, containing colorectal cancer, where it advances the migration and invasion of cancer cells [25]. Similarly, a previous study has proved that Wnt-11 expression is heightened in hormone-independent prostate cancer [26].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study has presented miR-410 expression was reduced in human estrogen receptor-positive tissues of breast cancer [24]. It is reported that secreted factor Wnt-11 expression is ascended in several types of cancer, containing colorectal cancer, where it advances the migration and invasion of cancer cells [25]. Similarly, a previous study has proved that Wnt-11 expression is heightened in hormone-independent prostate cancer [26].…”
Section: Discussionmentioning
confidence: 99%
“…A study has indicated that Wnt-11 expression heightened in cervical cancer cells may result in activation and phosphorylation of JNK-1 by activating Wnt/Jnk pathway and boosts the proliferation and migration/invasion of tumor cells [15]. It has been suggested that Wnt-11 gene silencing in colorectal cancer cell lines reduced the invasive ability of cells [25]. Furthermore, the overexpression of miR-410 can restrain the invasion, migration, proliferation, and epithelial mesenchymal transformation of osteosarcoma cells via directly targeting TRIM44 [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the first instance, these data give further credence to the results from the in vitro and tissue analyses. More broadly, as noted above, since functional Wnt-11 expression occurs in other cancers as well, its role in determining survival may be more widespread in oncology [57].…”
Section: Discussionmentioning
confidence: 99%
“…Among several soluble Wnt proteins, Wnt11 was found to be upregulated in CRC patients [ 84 ]. Recently, Gorroño-Etxebarria and colleagues [ 85 ] have shown that increased Wnt11, and its FZD6 , RYK, PTK7 receptors, positively correlate with poor prognosis. Additionally, Wnt11 downregulated β-catenin transcriptional activity and increased ATF2 via the non-canonical Wnt signalling pathway.…”
Section: Non-canonical Wnt Pathway and Crcmentioning
confidence: 99%